Heat transfer and pressure drop in laterally perforated-finned heat sinks across different flow regimes. (October 2017) - Shaeri, Mohammad Reza; Bonner, Richard
Abstract: Experiments were performed to investigate pressure drop and forced convection heat transfer from laterally perforated-finned heat sinks (LA-PFHSs) across a wide range of flow regimes ranging from laminar to turbulent. Perforations with square cross sections were implemented equidistantly along the lateral surfaces of the fins. Results were compared with those of the solid-finned heat sink (SFHS) that was used as the base of comparisons. Thermal-fluid characteristics were investigated under the changes in both perforation size and porosity. The pressure drag in LA-PFHSs was found as the dominant component of the total drag compared with the friction drag. Thermal performances of LA-PFHSs were categorized into three types of industrial demands that require overall colder heat sinks, more uniform temperature heat sinks, and lighter heat sinks. For this purpose, three performance parameters were defined, and each performance parameter was associated to a specific category of industrial demand. It was found that if the optimum range of porosities is obtained at a given perforation size, LA-PFHSs lower both thermal resistance and temperature non-uniformity across the heat sink base without increasing the pumping power. The excellent advantage of LA-PFHSs in weight sensitive applications was demonstrated through a new performance parameter as the mass-based thermal resistance, and 41–51% lower mass-based thermal resistance compared with that of the SFHS was achieved using LA-PFHSs with the maximum porosity, without increasing the pumping power.